Proposal for the implementation of methods engineering through the balancing of the assembly line in the production process of a textile apparel industry for women's denim garments - Lopez Zavaleta, Liz Madeleine (2022)
Over the years, the motion study method has been proved to be a powerful tool for process standardization in the textile industry, which enables determining the standard time for the performance of a specific task. Moreover, the processing time plays a pivotal role in the management of the production processes when applying the time study technique. Besides, the application of the assembly line balance constitutes a primary goal of manufacturing companies for producing vast quantities in the shortest possible time with satisfactory and efficient results. This research was conducted in a textile company that manufactures denim clothing for women, located in San Juan de Lurigancho District in Lima, Peru. It aims to reduce unproductive time in the production line caused by a poor productive process, excessive movements and long waiting times, by means of applying the method engineering and line balance. In order to obtain the required information for this research, Arena Simulation Software has been used for analyzing the cycle time, productivity and efficiency of small and medium enterprises (SMEs).